Global burden of disease study analysis of thyroid cancer burden across 204 countries and territories from 1990 to 2019 - Dou, Zhili; Shi, Yanyan; Jia, Jinzhu (Frontiers in Oncology, 2024)
The purpose of this study is to assess the burden of thyroid cancer over the course of 30 years in 204 countries and territories.Data from the Global Burden of Disease (GBD) 2019 database was analyzed to extract information on prevalence, deaths, DALYs(disability-adjusted life-years), YLL(years of life los), YLD(years lived with disability), and their corresponding agestandardized rates at global, regional, and national levels. The primary focus of the study was to examine trends in thyroid cancer from 1990 to 2019, specifically looking at the Estimated Annual Percentage Change (EAPC) for ASPR, ASDR, and ASDR.Additionally, the study investigated the relationship between cancer burden and the Socio-Demographic Index (SDI).Globally, there will be approximately 18.3 million thyroid cancer (TC) cases in 2019;China and the USA are projected to be the most significant with 310,327 and 220,711 cases (16.17 and 14.82 cases per 100,000 people, respectively).Over the period from 1990 to 2019, age-standardized prevalence rates exhibited a global rise, whereas deaths and DALYs saw a decrease(EAPC:1.63, -0.15--0.14, respectively).Significantly, the age-standardized prevalence rate increased in 21 GBD regions, affecting 195 out of 204 countries or territories. Over the studied period, thyroid cancer cases, deaths, and DALYs were consistently higher among females than males. Furthermore, a higher Socio-demographic Index was associated with increased agestandardized prevalence rates.